PENGARUH PELAPISAN DALAM MEMPERTAHANKAN VIABILITAS BENIH JAMBU BIJI MERAH (PSIDIUM GUAJAVA L.) SELAMA PENYIMPANAN - Vanisa Auliya; Maryati Sari; Okti Syah Isyani Permatasari (BPFP Universitas Bengkulu, 2026)
[EFFECT OF SEED COATING ON MAINTAINING VIABILITY OF RED GUAVA (Psidium guajava L.) SEEDS DURING STORAGE]. Guava (Psidium guajava L.) is one of the potential intercropping options for a revegetation programme. Hydrophilic polymer coating and several additional materials are expected to increase the vigor of seeds planted by direct sowing under suboptimal conditions. However, it is necessary to study its effect on seed viability during storage, especially on guava seeds which are classified as intermediate seeds.This study aims to determine the effect of coating on the viability of guava seeds (Psidium guajava L.) during storage. The experiment was arranged in a factorial randomized complete block design (RCBD) with two factors: coating materials (control, alginate, tapioca, alginate + manure pelleting, alginate + vermicompost pelleting, tapioca + manure pelleting, and tapioca + vermicompost pelleting) and storage periods (0, 2, and 4 weeks) in polyethylene bags. The results showed that storage for more than two weeks caused a sharp decrease in germination percentage and vigor index. Coating treatment with alginate for two weeks is more effective in maintaining water content, germination percentage, and seed vigor. Seed coating with alginate is recommended method for extending shelf life while maintaining the physiological quality of guava seeds. Pelleting using alginate and vermicomposting were not significantly different from coating treatment with alginate in the same parameters, so both treatments can be recommended as neede